ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND THE IMPACT OF ORGANIZATIONAL COMMITMENT AND WORK-LIFE BALANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE: Empirical Study by Utilizing SEM Lisrel and Qualitative Analysis on Millennial Employees of South Tangerang - Hermawati, Rahmi; Moeins, Anoesyirwan; Suhardi, Eka (jfpublisher, 2023)
Organizational citizenship behavior is considered ineffective since it is not balanced with a sufficient quality of work life, such as a comfortable working environment, a sufficient compensation, career advancement, and others. Furthermore, a lack of job satisfaction leads to many employees ignoring their work behavior. This research used a mixed method that systematically integrates quantitative and qualitative methods, with the first stage of the research utilizing quantitative methods and the second stage using qualitative ones. Subject data is the type of data utilized in this research (self-report). The information was gathered straight from the millennial employees of South Tangerang. The objective of this research is to find out efforts to increase organizational citizenship behavior by analyzing the influence of exogenous and intervening variables on organizational citizenship behavior. According to this research findings, there are some impacts of organizational commitment and work-life balance with job satisfaction, one of them is work-life balance will increase organizational citizenship behavior without the support of job satisfaction. In addition, there are four accepted hypotheses and three rejected hypotheses.